Analisis Kejadian Kelelahan Kerja Pada Karyawan di PT. Waskita Karya Proyek Makassar Sewrerage B2 - Sumasta, Nur Ainun; Rahman; Hardi, Ikhram (Window of Public Health Journal, 2025)
Work fatigue is a condition of decreased efficiency, work performance, and reduced body strength or physical endurance to continue the activities that must be done. Fatigue that occurs continuously results in chronic fatigue. This study aims to analyze the incidence of work fatigue in employees at PT. Waskita Karya Makassar Sewerage B2 Project. This type of research is quantitative research with a cross-sectional study design. The population of this study was 65 workers who worked at PT. Waskita Karya Makassar Sewerage B2 Project. A sample of 55 workers was taken using the accidental sampling method. Data were collected using questionnaires, scales, stature meters, stopwatches, and reaction timers. Data were analyzed using the chi-square test and spirmen correlation at a 95% confidence level (α = 0.05). This study's results indicate a relationship between age and work fatigue (p = 0.042). There is a relationship between nutritional status and work fatigue (p = 0.029) in employees at PT. Waskita Karya Makassar Sewerage B2 Project in 2023. This study concludes that age, workload, work environment, and nutritional status are related to the occurrence of work fatigue in employees at PT. Waskita Karya Makassar Sewerage B2 Project, and the length of service variable has no relationship with the occurrence of work fatigue in employees at PT. Waskita Karya Makassar Sewerage B2 Project.